2016
DOI: 10.1021/acs.jpcc.6b05091
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, and Li Migration Properties of RE-Doped (RE = Ce, La) LiCoO2for Li-ion Batteries: A First-Principles Investigation

Abstract: Rare earth elements, known for their large radius, high charge, and strong self-polarization ability, are expected to bring improvements in Li-ion batteries. However, some basic issues such as structural variation, the nature of the improved Li mobility, and electronic conductivity in rare earth-doped electrode compounds are still unrevealed. In the present work, the structural, electronic, and Li migration properties of Ce-and La-doped LiCoO 2 cathode materials are systematically studied by using the first-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 41 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…3e and f and S7 (ESI † ). 26 It can be seen that NTO shows a direct bandgap of 3.07 eV while the bandgap of NTO:Yb decreased to 0.58 eV, which indicates that the polaron migration energy barrier along the constrained pathway is decreased, 25 thus attributing to a larger electronic conductivity of NTO:Yb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3e and f and S7 (ESI † ). 26 It can be seen that NTO shows a direct bandgap of 3.07 eV while the bandgap of NTO:Yb decreased to 0.58 eV, which indicates that the polaron migration energy barrier along the constrained pathway is decreased, 25 thus attributing to a larger electronic conductivity of NTO:Yb.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the crystal lattice distortion owing to the introduction of lanthanide ions will give rise to the generation of oxygen vacancies. 25 The reaction for oxygen vacancy formation using Kroger–Vink notation can be expressed as: …”
Section: Resultsmentioning
confidence: 99%
“…4 shows the spin polarized band structure, from which the impurity states at the edge of Fermi level can be seen. Band decomposed charge densities are also given [77] .…”
Section: Effect Of Cation Dopingmentioning
confidence: 99%
“…Band structure and band decomposed charge density of Ce doped LiCoO 2 and La doped LiCoO 2 (Published with the permission from ACS)[77] .…”
mentioning
confidence: 99%
“…However, in some cases, metal ions are able to replace one another in a limited range of compositions, although the difference in their radii exceeds 60% [10]. The influence of the Ce 4+ -and La 3+ -doping on the crystal and electronic structure of LiCoO 2 has been investigated by the first-principles calculations [11]. The results indicated that Ce 4+ and La 3+ -doped LiCoO 2 has expanded Li + slab distances, thus decreasing the Li + migration energy barrier; the diffusion coefficient was improved by 4 and 7 orders of magnitude, respectively.…”
Section: Introductionmentioning
confidence: 99%